Nonoscillatory Solutions of Second-Order Superlinear Dynamic Equations with Integrable Coefficients. (6th February 2012) - Lin, Quanwen; Jia, Baoguo
Abstract : The asymptotic behavior of nonoscillatory solutions of the superlinear dynamic equation on time scales ( r ( t ) x Δ ( t ) ) Δ + p ( t ) | x ( σ ( t ) ) | γ sgn x ( σ ( t ) ) = 0, γ > 1, is discussed under the condition that P ( t ) = lim τ → ∞ ∫ t τ p ( s ) Δ s exists and P ( t ) ≥ 0 for large t .